Viscoelastic characteristic iron powder core for reducing vibration and noise radiated by switched reluctance machine. (2021) - Vijayakumar, K.; Saravanan, P.; Basanth, A. Joseph; Karthikeyan, R.; Rajendirakumar, R.
Abstract: This paper presents a new direction on the mitigation of acoustic noise and vibration in a switched reluctance machine using viscoelastic property of iron powder material also known as SMC – Soft Magnetic Composite. SMC material is made of iron powder particles whose surface is insulated by an oxide layer which is continuous. With a lubricant and a binder at high pressure these particles are compacted to result a bulk material. Soft magnetic composite material is characterized by the ferromagnetic property which is isotropic and three dimensional. The reduction in eddy current loss can be attributed to the insulation coating which is tantamount to the increase in resistance in laminated core. The reduced ripple torque due to soft magnetic electrical core is because of isotropic distribution of magnetic particles. The finite element method (FEM) based simulation studies on torque ripple, vibration and noise has been described. The test results of prototype SMC-SRM, vibration and performance results have been analyzed to validate the simulation results. The study, analysis and experimentation concludes that use of SMC as core in a SRM results in reduced vibration and noise.